1998
DOI: 10.1520/jfs14371j
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Typology for the Biopsychosociocultural Evaluation of Child-Killing Behavior

Abstract: requires an approach where different potential causes for such Weinstock R, Yamamoto J. A comprehensive typology for the behavior are explored, resulting in the need to develop taxonomies. biopsychosociocultural evaluation of child-killing behavior. J Classification schemes for child-killing behavior have been pro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Fourth, some studies raise validity concerns owing to the use of sources containing data from individuals who, at inclusion, had merely been arrested under the suspicion of having committed child homicide (see, for example, [Eke, Basoglu, Bakar, & Oral, 2015;Mariano, Chan, & Myers, 2014]). Finally, a number of prior attempts have been made to classify child homicide into meaningful categories in order to facilitate preventive action; unfortunately, the usefulness of many proposed typologies is limited by a considerable overlap between categories (Putkonen et al, 2016;Silva et al, 1998).…”
Section: Common Methodological Challenges In Child-homicide Researchmentioning
confidence: 99%
“…Fourth, some studies raise validity concerns owing to the use of sources containing data from individuals who, at inclusion, had merely been arrested under the suspicion of having committed child homicide (see, for example, [Eke, Basoglu, Bakar, & Oral, 2015;Mariano, Chan, & Myers, 2014]). Finally, a number of prior attempts have been made to classify child homicide into meaningful categories in order to facilitate preventive action; unfortunately, the usefulness of many proposed typologies is limited by a considerable overlap between categories (Putkonen et al, 2016;Silva et al, 1998).…”
Section: Common Methodological Challenges In Child-homicide Researchmentioning
confidence: 99%
“…psychotherapy, art therapy/psychodrama) also proved useful in developing understanding, and providing a conduit for addressing filicide (West and Friedman, 2007). Furthermore, it is argued that conscious and unconscious processes, as well as individual and social factors, should be explored (Silva et al , 1998). This is supported by participants in the current study, as they generally experienced a deeper level of insight about positive and negative life experiences, and were more able to develop critical thinking and skills to manage problematic feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Since the perceived intention of the perpetrator may have significant legal implications, there may be deliberate efforts at deception regarding the true motivation of the crime. Finally, it has been argued that the failure to address the social and cultural environment in which the killing took place prevents this typology from being used for a systematic evaluation of filicide (Silva, 1998).…”
Section: Methods Of Classificationmentioning
confidence: 99%
“…Silva et al (1998) noted that other classification systems failed to evaluate the relevant cultural and environmental factors that underlie filicide. The authors suggested a multilevel approach in which filicides are described by a combination of factors based on psychiatric diagnosis, developmental issues of victim and perpetrator, and behavioral factors as well as the stressors faced by the parent in his or her demographic and cultural context.…”
Section: Methods Of Classificationmentioning
confidence: 99%